Pengaruh E-readiness, E-learning dan E-book pada Implementasi Kurikulum Program Studi D3 Teknologi Mesin terhadap Prestasi Lulusan Program Diploma - C Rudy Prihantoro (JTP - Jurnal Teknologi Pendidikan, 2018)
This research is to find out; the influence of e-readiness, e-learning, ebook on the achievement of graduates of diploma programs; and the influence of ereadiness, e-learning, and e-books on the achievement of diploma program graduates. The study population was graduates of the D3 Mechanical TechnologyStudy Program, Faculty of Engineering, Jakarta State University, the sample was the second semester of the 2016/2017 academic year. Data collection usesperceptual instruments for electronic readiness, e-books, and e-books, and relevant graduate GPA. The research method is a survey method with an associativeapproach. Data analysis techniques are simple regression, double freedom, and F test. The results of the study show; (1) there is no effect of e-readiness on Graduates' Achievement; (2) there is no influence of e-learning on graduate achievement; (3) there is no e-book effect on Graduates' Achievement; (4) there is no effect of ereadiness, e-learning and e-books together for the achievement of graduates. There is no provision in this study that can be interpreted that the curriculum developed by the D3 Mechanical Technology Study Program is in accordance with Learning Outcomes, especially in the implementation of the learning process.